Pengaruh Pemberian Kudapan Berbasis Ikan terhadap Peningkatan Kadar Hemoglobin pada Remaja Putri yang Mengalami Anemia - Sari, Diesna; Fauziah, Fauziah (Universitas Batanghari Jambi, 2025)
The purpose of this study was to determine the effect of fish-based snacks on increasing hemoglobin (Hb) levels in adolescent girls with anemia. The study was conducted using the Quasi Experiment method with a randomized pretest-posttest control group design. The population was all female students with anemia at SMPN 1 Campalagian who were obtained from the results of hemoglobin level examinations using an Hb-meter and were willing to become respondents by filling out informed consent. Sampling was carried out using probability sampling. The treatment group was given fish-based snacks and iron tablets, while the control group was only given iron tablets for 4 weeks each. The research data were analyzed using the Kruskall-Wallis test. The results of the study on the Hb levels of subjects in each group increased significantly, allegedly because both groups received intensive iron tablet intervention from the school, so that both showed improvements in blood hemoglobin levels. The body weight (BW) and nutritional status of the subjects did not show significant differences until the end of the intervention, but based on the difference in changes in body weight (BW) in the treatment group there was a tendency for improvement compared to the control group with weight gain (BW). Providing high protein intake will affect weight gain and can significantly affect the hemoglobin (Hb) levels in the blood of adolescent girls.